2023
DOI: 10.3390/ijms24076548
|View full text |Cite
|
Sign up to set email alerts
|

Those That Remain: Sorption/Desorption Behaviour and Kinetics of the Neonicotinoids Still in Use

Abstract: In January 2023, the derogation loophole was closed on “emergency authorisations” for the use of three out of five neonicotinoids in all EU states. In this study, we analysed the sorption/desorption behaviour and kinetic parameters of acetamiprid and thiacloprid, the two neonicotinoids that are still approved for use, either regularly or under emergency authorisations in the EU, and widely used worldwide. Sorption and desorption curves in four soils with different organic matter content were analysed using fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…To estimate the time needed to achieve sorption and desorption equilibrium, the sorption and desorption kinetics of acetamiprid, imidacloprid, and thiacloprid (30 mg/L) were monitored at 20 (±1) °C for a time frame of 96 h. The results of the sorption/desorption study are presented in our previous publication [ 53 ]. In our studies, the sorption kinetics showed rapid initial insecticidal sorption within the first few hours, depending on the insecticide, and the equilibrium was reached within 47 h, while the equilibrium for the desorption reactions was reached within 94 h. The sorption and desorption processes were conducted for 96 h, and this time was sufficient to reach equilibrium conditions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To estimate the time needed to achieve sorption and desorption equilibrium, the sorption and desorption kinetics of acetamiprid, imidacloprid, and thiacloprid (30 mg/L) were monitored at 20 (±1) °C for a time frame of 96 h. The results of the sorption/desorption study are presented in our previous publication [ 53 ]. In our studies, the sorption kinetics showed rapid initial insecticidal sorption within the first few hours, depending on the insecticide, and the equilibrium was reached within 47 h, while the equilibrium for the desorption reactions was reached within 94 h. The sorption and desorption processes were conducted for 96 h, and this time was sufficient to reach equilibrium conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A discrepancy between the sorption and desorption isotherms for imidacloprid in Croatian soils was found in our previous publication. For all analyzed soils, the H values were lower than 1, and we found that the hysteresis was more pronounced in soils with a higher content of OM, primarily humic acids [ 53 ]. Cox et al [ 66 ] point out the important fact that soil with a stronger sorption capacity at higher imidacloprid concentrations showed higher desorption compared to other soils, which was also confirmed by a higher hysteresis coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations